Polarity Umpolung Strategy for the Radical Alkylation of Alkenes. Issue 21 (11th March 2020) - Liu, Jige; Wu, Shuo; Yu, Jiajia; Lu, Chenxi; Wu, Zhen; Wu, Xinxin; Xue, Xiao‐Song; Zhu, Chen
Abstract: Free radical mediated alkylation of alkenes is a challenging and largely unmet goal. Disclosed here is a conceptually novel "polarity umpolung" strategy for radical alkylation of alkenes using a portfolio of easily accessed, difunctional alkylating reagents. This strategy is achieved by substituting inherently nucleophilic alkyl radicals with electrophilic sulfone‐bearing surrogates, thus inverting the usual mode of reactivity. Along with alkylation, either an heteroaryl or oximino group is concurrently incorporated into the alkenes by a consecutive docking and migration process, leading to valuable products. The reaction displays a broad functional‐group tolerance under mild reaction conditions. The protocol opens new vistas for the late‐stage modification of complex natural products and drug molecules containing alkene moieties. Abstract : Polarity switch : A novel, mild, easy‐to‐execute protocol for radical alkylation of alkenes was developed using a polarity umpolung strategy. Both activated and challenging unactivated alkenes are suitable substrates. The protocol opens new vistas for the late‐stage modification of complex natural products and drug molecules containing alkene moieties.